2016
DOI: 10.1039/c5fo00758e
|View full text |Cite
|
Sign up to set email alerts
|

The role of plant cell wall encapsulation and porosity in regulating lipolysis during the digestion of almond seeds

Abstract: Previous studies have provided evidence that the physical encapsulation of intracellular nutrients by cell walls of plant foods (i.e. dietary fibre) plays a predominant role in influencing macronutrient bioaccessibility (release) from plant foods during human digestion. One unexplored aspect of this is the extent to which digestive enzymes can pass through the cell-wall barrier and hydrolyse the intracellular lipid in almond seeds. The purpose of the present study was to assess the role played by cell walls in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 76 publications
(52 citation statements)
references
References 51 publications
(77 reference statements)
2
50
0
Order By: Relevance
“…This swelling of the cell wall may explain why intact cells lose lipid after longer retention times, suggesting that lipase, colipase and bile salt could diffuse into the intracellular compartment and then initiate lipolysis. However, lipase does not seem to diffuse through the intact cell walls even after prolonged incubation times (up to 20 h) as demonstrated by in vitro digestion experiments performed on laboratory-separated almond cells (Grundy et al, 2016). Nevertheless, in small particles of masticated almond, there was some evidence of rupture and fissures in 'damaged cells' underlying the fractured surface and this may account for the lipid release that occurs after prolonged incubation in the GI tract (Mandalari et al, 2008a;Grundy et al, 2015a).…”
Section: Digestion Of Whole Raw Almondsmentioning
confidence: 98%
See 4 more Smart Citations
“…This swelling of the cell wall may explain why intact cells lose lipid after longer retention times, suggesting that lipase, colipase and bile salt could diffuse into the intracellular compartment and then initiate lipolysis. However, lipase does not seem to diffuse through the intact cell walls even after prolonged incubation times (up to 20 h) as demonstrated by in vitro digestion experiments performed on laboratory-separated almond cells (Grundy et al, 2016). Nevertheless, in small particles of masticated almond, there was some evidence of rupture and fissures in 'damaged cells' underlying the fractured surface and this may account for the lipid release that occurs after prolonged incubation in the GI tract (Mandalari et al, 2008a;Grundy et al, 2015a).…”
Section: Digestion Of Whole Raw Almondsmentioning
confidence: 98%
“…These results strengthen the assumption that by increasing the number of fractured cells through either processing or mastication, the bioaccessibility of nutrients, especially lipids, is enhanced. More recent studies have confirmed that almonds consumed as the whole kernel (raw or roasted) were not fully digested, and the lipids were released slowly during the digestion process (Grassby et al ., ; Mandalari et al ., ; Grundy et al ., ,b, ). This behaviour is strongly linked to the resistance of almond tissue/cell walls to chemical and physical breakdown in the mouth, stomach and small intestine.…”
Section: Behaviour Of Whole and Processed Almonds In The Gi Tract Andmentioning
confidence: 99%
See 3 more Smart Citations